The formalization of geometrical, calculation and tehnological informations as the base for CAD/CAM oriented programming systems (2-nd part.) - Gatalo, Risto; Zeljković, Milan; Hodolič, Janko; Borojev, Ljubomir; Rekecki, Jožef; Slobodan, Čabarkapa; Navalušić, Slobodan (Journal of Production Engineering, 1986)
This paper is a continuation of the paper with the same title published in this journal 1984 (No. 1). In this paper, we consider the geometry of a symbolic language for describing non-rotational shapes on rotational parts, as well as the technology of symbolic language and its various elements. We compare the integral version of SAPOR Symbolic Language to previous versions, particularly focusing on the analysis of the possibility of further improvement and generalization of the integral concept of SAPOR symbolic language. We delve into aspects such as the formalization of input formations for specific and special geometrical forms, formalization of computational information, and the utilization of special alternative language elements.